Thermal Conductivity of Plantation Wood Species and Selected Tropical Hardwoods from the Philippines - Mario Angelo M. Mundin; Menandro N. Acda (BioResources, 2025)
This study investigated the transverse thermal conductivity of low-density plantation wood species and tropical hardwoods from the Philippines using the guarded hot-plate method. Results showed that thermal conductivity of low density, plantation species and denser tropical hardwoods ranged from 0.128 to 0.188 W/mK and 0.161 to 0.300 W/mK, respectively. Thermal conductivity was directly influenced by both density and moisture content of wood. Transverse thermal conductivity increased by 0.73% and 1.79% per percent increase in MC from 0% to 21% MC for low density (<500 kg/m3) and high density (>500 kg/m3) wood, respectively. Linear regression models fitted for thermal conductivity and ovendry density indicated a strong fit. However, there was a poor to moderate relationship between thermal conductivity and MC. The results of the present study may be of interest in the conversion of woody biomass to bioenergy or to building designers looking for natural materials to improve energy performance and efficiency of wood structures where heat transfer and temperature control are a significant economic consideration.